LIBBY’S DEPRESSION AS SEEN IN JENNIFER NIVEN’S HOLDING UP THE UNIVERSE - Handoko, Putut; Firdaus, Ghina Arifah (Dinamika : Jurnal Sastra dan Budaya, 2017)
The thesis writer focuses on the analysis of Libby?s Depression as seen in Jennifer Niven?s Holding Up The Universe. The objectives of the study are, to find out the types of Libby's Depression, the causal factors of Libby's Depression and the effects of Libby's Depression as see in Jennifer Niven's Holding Up The Universe on herself, the society, and Jack Masselin. The thesis writer applies the theory of concept of depression, sign and symptoms of depression, the causes of depression, and she also applies a qualitative research. Keywords: Depression